2020
DOI: 10.1371/journal.pgen.1008565
|View full text |Cite
|
Sign up to set email alerts
|

Technical and social issues influencing the adoption of preprints in the life sciences

Abstract: Preprints are gaining visibility in many fields. Thanks to the exponential growth in submissions to bioRxiv, an online server for preprints in biology, versions of manuscripts prior to the completion of journal-organized peer review are poised to become a standard component of the publishing experience in the life sciences. Here, we provide an overview of current challenges facing preprints, both technical and social, and a vision for their future development. Unbundling the functions of publication Science pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…2B). Further studies on understanding the motivations behind posting preprints, for example through quantitative and qualitative author surveys may help funders and other stakeholders that support the usage of preprints to address some of the social barriers for their uptake [30]. bioRxiv and medRxiv included a banner to explain that preprints should not be regarded as conclusive and not reported on in the news media as established information [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Further studies on understanding the motivations behind posting preprints, for example through quantitative and qualitative author surveys may help funders and other stakeholders that support the usage of preprints to address some of the social barriers for their uptake [30]. bioRxiv and medRxiv included a banner to explain that preprints should not be regarded as conclusive and not reported on in the news media as established information [31].…”
Section: Discussionmentioning
confidence: 99%
“…This advantage may influence the dynamics of preprint uptake: as researchers in a given field begin to preprint, their colleagues may feel pressure to also preprint in order to avoid being scooped. Further studies on understanding the motivations behind posting preprints, for example through quantitative and qualitative author surveys may help funders and other stakeholders that support the usage of preprints to address some of the social barriers for their uptake [28].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the number of arXiv preprint authorships increased between 2019 and 2020 for all authorship positions and genders ( Figure 1). Increases in preprint submissions between 2019 and 2020 are perhaps not surprising, as scientific output and the popularity of preprint servers have both been increasing in recent years (Penfold & Polka, 2020), and the time-sensitive nature of COVID-19 research may also have encouraged greater use of preprint servers among scientists (Fraser et al, 2020). On the other hand, we might have expected decreased productivity overall during the pandemic because of illness and bereavement, and also laboratory closures impacting experimental scientists.…”
Section: Year-over-year Comparison Of Arxiv Preprint Submissionsmentioning
confidence: 99%
“…Peer review takes time, so it is still too soon to see the full effect of COVID-19 on the numbers of journal articles published by women versus men academics. However, a growing number of academics make their submitted or in-progress manuscripts available on preprint servers (Penfold & Polka, 2020), making it possible to measure the pandemic's effect on preprint submissions in real time. Preliminary evidence also suggests a growing importance for preprints during the pandemic, as there is a high demand for rapid research to understand COVID-19 (Fraser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The preprint platforms were widely explored as hubs for disseminating scientific findings [6], especially for early-stage researchers [7], which revealed a number of social and technical issues associated with their adoption [8]. The top four concerns with preprint servers included scooping of scientific results [9], poor data quality [10], spread of misinformation [11], and varied and non-transparent deposition policies [6].…”
Section: Introductionmentioning
confidence: 99%